ENGLISH ROMANTICISM AND ITS DEVELOPMENT - Tuychiboeva Shakhlo Zayniddin qizi, Elvina Reshatovna Kenjali (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Western culture was profoundly impacted by the literary movement known as English Romanticism, which took place during the late 18th and mid-19th centuries. Romanticism arose in response to social upheavals, accepting the various viewpoints of people and supporting the common man. It was rooted in a deep respect for nature, a celebration of individualism, and an investigation of strong emotions. This article examines the key elements of Romanticism, such as its emphasis on spirituality, nature, seclusion, and the idealization of women, in addition to its key proponents, including Byron, Shelley, Coleridge, Wordsworth, and others. By questioning established conventions and encouraging future generations to seek beauty, truth, and the sublime via their works, the Romantics left a lasting legacy that is still relevant in today's artistic discourse.